Fetal middle cerebral artery and umbilical artery pulsatility index: effects of maternal characteristics and medical history. (April 2015) - Akolekar, R.; Sarno, L.; Wright, A.; Wright, D.; Nicolaides, K. H.
ABSTRACT Objective To define the contribution of maternal variables which influence the measured fetal middle cerebral artery (MCA) and umbilical artery (UA) pulsatility index (PI) in the assessment of fetal wellbeing. Methods Maternal characteristics and medical history were recorded and fetal MCA‐PI and UA‐PI (n = 36 818) were measured in women with singleton pregnancies attending a routine hospital visit at 30 + 0 to 37 + 6 weeks' gestation. For pregnancies delivering phenotypically normal live births or stillbirths ≥ 30 weeks' gestation, variables among maternal demographic characteristics and medical history that are important in the prediction of MCA‐PI and UA‐PI were determined by multiple linear regression analysis. Results Significant independent contributions to MCA‐PI were provided by gestational age at assessment, East Asian racial origin, being parous and birth‐weight Z‐score of the neonate of the previous pregnancy. Significant independent contributions to UA‐PI were provided by gestational age at assessment, Afro‐Caribbean, East Asian and mixed racial origin, cigarette smoking, being parous and birth‐weight Z‐score of the neonate of the previous pregnancy. Multiple linear regression analysis was used to define the contribution of maternal variables that influence the measured MCA‐PI and UA‐PI and express the values as multiples of the median (MoMs). The cerebroplacental ratio (CPR) MoM was calculated by dividing MCA‐PI MoM by UA‐PI MoM. The model was shown to provide an adequate fit of MoM values for all covariates, both in pregnancies that delivered small‐for‐gestational‐age neonates and in those without this pregnancy complication. Conclusions A model was fitted to express MCA‐PI, UA‐PI and CPR as MoMs after adjusting for variables from maternal characteristics and medical history that affect this measurement. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.